2015
DOI: 10.1111/adb.12290
|View full text |Cite
|
Sign up to set email alerts
|

Transient CNS responses to repeated binge ethanol treatment

Abstract: Adaptive changes occur in response to repeated exposure to drugs. Although ethanol (EtOH) is known to induce pharmacokinetic tolerance, the effects of EtOH on in vivo, magnetic resonance (MR)-detectable brain measures across repeated exposures have not previously been reported. Of 28 rats weighing 341±22g at baseline, 15 were assigned to the EtOH group and 13 to the control (Ctrl) group. EtOH animals were exposed to 5 cycles of 4-days of EtOH treatment followed by 10 days of recovery. Rats in both groups had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 106 publications
(121 reference statements)
3
17
2
1
Order By: Relevance
“…For example, following short-term administrations of cocaine (Li et al, 2012) or alcohol (Zahr et al, 2015), rats showed transient striatal (Li et al, 2012) or whole-brain (Zahr et al, 2015) increases in glutamate and/or GABA [but see (Lee et al, 2014)]. Such results are consistent with the idea that addiction-related decreases in glutamate or GABA could reflect neuroadaptations to chronic drug exposure.…”
Section: 0 Working Hypothesis: Abnormal Glutamatergic And/or Gabaesupporting
confidence: 53%
“…For example, following short-term administrations of cocaine (Li et al, 2012) or alcohol (Zahr et al, 2015), rats showed transient striatal (Li et al, 2012) or whole-brain (Zahr et al, 2015) increases in glutamate and/or GABA [but see (Lee et al, 2014)]. Such results are consistent with the idea that addiction-related decreases in glutamate or GABA could reflect neuroadaptations to chronic drug exposure.…”
Section: 0 Working Hypothesis: Abnormal Glutamatergic And/or Gabaesupporting
confidence: 53%
“…Although the TE group did not show statistically significant group effects, lateral ventricle and total CSF volumes were enlarged following the first EtOH exposure period. Unlike our repeated EtOH exposure experiment (Zahr et al 2015b), however, there was a relatively suppressed effect of the second EtOH exposure on lateral ventricular volume in the TE group. One potential explanation for the attenuated effect of the second EtOH treatment is that these EtOH-exposed animals were being given daily injections of thiamine.…”
Section: Discussioncontrasting
confidence: 84%
“…Animal models can be used to distinguish components of the processes associated with damage to the brain in response to alcohol exposure (Pfefferbaum et al 2008; Zahr et al 2010b; Zahr et al 2014b; Zahr et al 2013; Zahr et al 2009b; Zahr et al 2015b). Our in vivo magnetic resonance imaging (MRI) studies of rats have consistently shown increases in cerebrospinal fluid (CSF) volumes following ethanol (EtOH) exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les développements techniques en informatique et e-santé permettent d'envisager de nouvelles méthodes de monitoring de la consommation d'alcool chez les patients, en utilisant par exemple des applications Smartphone [42]. De manière complémentaire, les études conduites chez l'animal permettent de modéliser les différents profils d'évolution des consommations (abstinence totale, binge, consommation faible mais régulière) et permettent ainsi d'examiner des groupes d'animaux avec un profil de consommation homogène [43].…”
Section: Complémentarité Des Approches Cliniques Et Précliniquesunclassified